2017
DOI: 10.1001/jama.2017.9924
|View full text |Cite
|
Sign up to set email alerts
|

Updated Cost-effectiveness Analysis of PCSK9 Inhibitors Based on the Results of the FOURIER Trial

Abstract: A cost-effectiveness analysis of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors based on their lowering of low-density lipoprotein cholesterol (LDL-C) demonstrated that the 2015 price of PCSK9 inhibitors would need to be reduced by more than two-thirds (to $4536 per year) to meet generally accepted cost-effectiveness thresholds. 1 Since that report, the Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) trial found the PCSK9 inhibitor evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
171
1
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(179 citation statements)
references
References 2 publications
4
171
1
3
Order By: Relevance
“…24,25 In addition, some states have passed legislation requiring standardized PA forms across drug classes, which may also influence PA policies for PCSK9is in the future. Further research is needed to understand how PA requirements impact prescribing and initiation of PCSK9is and how this affects cardiovascular outcomes in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In addition, some states have passed legislation requiring standardized PA forms across drug classes, which may also influence PA policies for PCSK9is in the future. Further research is needed to understand how PA requirements impact prescribing and initiation of PCSK9is and how this affects cardiovascular outcomes in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This statin analysis was based on a lower-potency statin that was still patented; hence, a similar analysis performed today with high-potency generic statins would give even more favourable results. In a similar analysis involving the subsequent addition of ezetimibe to a statin, Kazi and colleagues 19 estimated a cost of US$199 000 per quality-adjusted life-year (QALY) compared to a statin alone. These results underscore the challenges associated with identifying cost-effective lipid therapies when compared with the low cost and demonstrated effectiveness of statins.…”
Section: Discussionmentioning
confidence: 99%
“…Arrieta and colleagues 20 published an updated model estimating a cost of US$337 729 per QALY and requiring a discount to $5459 per year to reach US$100 000 per QALY. Similarly, Kazi and colleagues 19 updated earlier estimates to US$339 000 per QALY, requiring a discount to US$4215 to achieve US$100 000 per QALY when comparing to the addition of ezetimibe. Importantly, those authors also confirmed that the estimated cost per life-year saved was lower than the cost per QALY.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, results from the ODYSSEY cardiovascular outcome trial (CVOT) support these findings, demonstrating a 3.4% absolute risk reduction in MACE in patients treated with PCSK-9 antibody to mean LDL of53.3 mg/dl, compared with LDL of 101.4 mg/dl in the placebo group [17]. Given their high cost and difficult insurance approval process [18], PCSK-9 antibody use is currently limited to patients with heterozygous familial hypercholesterolemia who are statin intolerant, or who have clinical ASCVD requiring additional lowering of LDL. One interesting PCSK9 inhibitor effect that needs further investigation, and could broaden its role in dyslipidemia management, is its ability to lower Lp(a); the degree in lowering may vary from patient to patient [19].…”
Section: Combination Therapiesmentioning
confidence: 99%